Genotypic Variations in Stomatal Regulation and Root Traits and their Association with Yield Parameters in Mot - Talwar, H S; Soni, M L; Beniwal, R K; Yadava, N D; Singh, J P; Rathore, V S; Rathore, V S; Kumar, Sunil (Annals of Arid Zone, 2016)
The experiments were conducted during kharif 2003 and 2004 seasons to analyze the genotypic variations in stomatal regulation and root traits and their association with yield parameters in moth bean (Vigna aconitifolia Jacq.) under water scarcity conditions of arid zone. Wide range of variations in total dry matter (TDM), pod yield (PY) and seed yield (SY) were noticed among the 26 genotypes. Our results suggest that genotypes with thick leaves (low SLA) exhibit more drought tolerance by keeping their stomata open at lower relative water content (RWC) in leaves. Significant relationship of specific leaf area (SLA) with both seed yield (r2= 0.57) and relative water content (RWC) (r2= 0.49) suggested that low SLA could be an important leaf trait for selecting moth bean genotypes for higher yield under water-deficit conditions. The strong relationship of specific root weight (SRW, root weight per unit root length) with TDM (r2= 0.73) and PY (i= 0.56) indicated that selection of genotypes with extensive root system would enhance the yield of moth bean under water scarcity conditions of arid zone. This study suggested that SLA, a cost-effective and easily measurable leaf trait, and/or SRW are the potential selection criteria to enhance the moth bean yield under rainfed conditions of the arid zone. Key words: Arid zone, moth bean, pod yield, root length, root weight, seed yield, specific leaf area, specific root weight, total dry matter.